The Psychosexual Impact of Postmastectomy Breast Reconstruction. Issue 5 (November 2016) - Hart, Alexandra M.; Pinell-White, Ximena; Losken, Albert
Abstract : Background: The surgical management of breast cancer with mastectomy and breast reconstruction (BR) has been shown to increase the quality of life of cancer survivors. Yet the impact of surgery on sexuality, femininity, and condition of intimate relationships as a measure for sexual health has not been fully evaluated. Methods: Ninety-six women who underwent mastectomy and immediate BR participated in the series. Surveys assessed patients' level of sexual health in the areas of femininity, sexual confidence during intimate relationships, and the role of breast sensibility in sexual satisfaction as compared with how they felt preoperatively. Surveys were scored on a 5-point Likert scale (5 = strongly agree). Inclusion criteria included longer than 1 year follow-up. Results: After BR, the majority felt that their breasts were as important to self-confidence (86.3%), femininity (84.0%), and sexuality (61.5%) as they were preoperatively. Women older than 50 years were more likely to feel that their breasts were not a significant part of their femininity (26.7% vs 11.8%, P = 0.05). Women with a BMI greater than 30 were more likely to feel that their partner's view of their breasts did not affect their self-confidence (46.2% vs. 20.7% P = 0.027). Women with a BMI less than 30 (23.2% vs 4.0%, P = 0.05), and those who had a major complication (22.2% vs 0.00%, P = 0.08) were more likely to disagree that nipple aerolar complex reconstruction improved their sexual confidence. Conclusions: Most women agree that their sexuality, femininity, and intimate relationships are maintained after BR. Increasing age and BMI may lead to changes in sexual health postoperatively.